INVESTIGATION OF CIRCULATING FACTORS AS MEDIATORS OF MUSCLE MITOCHONDRIAL BIOENERGETIC CHANGES ASSOCIATED WITH AGING, DIET, AND EXERCISE - Gonzalez-Armenta, Jenny Leigh (Wake Forest University, 2021)
As older adults continue to live longer and, as a result, with more comorbidities, there is a need to understand the cellular and molecular processes, including mitochondrial dysfunction, that are implicated in healthy aging and age-related diseases. Our lab and others have pioneered the use of blood cells as reporters of systemic mitochondrial bioenergetic capacity based on the premise that these circulating cells are continuously exposed to a myriad of factors that mediate bioenergetic capacity across multiple tissues. In support of this theory, our lab has demonstrated that blood cell mitochondrial bioenergetics can recapitulate the bioenergetics of brain, skeletal muscle, and cardiac muscle and that increased circulating IL-6 is associated with decreased mitochondrial bioenergetic capacity in blood cells. However, direct evidence supporting the effect of circulating factors on bioenergetics is limited. Therefore, the overarching hypothesis of my work is that there are circulating factors in blood associated with aging (and consequently, age-related diseases and interventions to improve healthspan) that can mediate systemic bioenergetic capacity. In Chapter Two, we found that long-term consumption of a Western diet resulted in elevated skeletal muscle mitochondrial bioenergetics of female cynomolgus macaques when compared to Mediterranean diet and that increased respiration was associated with increased insulin resistance, particularly with Western diet. In Chapter Three, we used a heterochronic parabiosis mouse model to investigate the effects of circulating factors on mitochondrial structure and function. We found a greater negative effect of old blood on young heterochronic mice, demonstrating the profound deleterious effects of circulating factors from old mice on mitochondrial structure and function. In Chapter Four, we developed a novel in vitro method to determine the effects of human serum from older adults who completed resistance training or resistance training plus caloric restriction interventions on muscle cells. We demonstrated that our method recapitulated the expected results of the intervention, i.e. improved bioenergetic capacity and differences between intervention groups, and identified potential circulating factors responsible for mediating mitochondrial bioenergetics associated with diet and exercise intervention. Taken together, this body of work provides evidence that circulating factors mediate bioenergetic capacity in multiple contexts: aging, diet, and exercise.
Keywords: aging and older adults; heterochronic parabiosis; mitochondrial bioenergetics; resistance training and caloric restriction; skeletal muscle; Western and Mediterranean diet